2015
DOI: 10.7554/elife.08494.026
|View full text |Cite
|
Sign up to set email alerts
|

Author response: Spatially coordinated dynamic gene transcription in living pituitary tissue

Abstract: Transcription at individual genes in single cells is often pulsatile and stochastic. A key question emerges regarding how this behaviour contributes to tissue phenotype, but it has been a challenge to quantitatively analyse this in living cells over time, as opposed to studying snap-shots of gene expression state. We have used imaging of reporter gene expression to track transcription in living pituitary tissue. We integrated live-cell imaging data with statistical modelling for quantitative real-time estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The analysis presented in the main paper has been calculated from the set of all possible transcriptional profiles, weighted by their probability of occurrence. Data of d2EGFP fluorescence measured in single cells and subsequent stochastic switch modelling of transcription activity have been deposited in the Dryad data repository ( Featherstone et al, 2015 )…”
Section: Methodsmentioning
confidence: 99%
“…The analysis presented in the main paper has been calculated from the set of all possible transcriptional profiles, weighted by their probability of occurrence. Data of d2EGFP fluorescence measured in single cells and subsequent stochastic switch modelling of transcription activity have been deposited in the Dryad data repository ( Featherstone et al, 2015 )…”
Section: Methodsmentioning
confidence: 99%
“…In the last several years, developmental studies have also shown that the level of cell-to-cell transcriptional variability among tissues is controlled by cellular interactions. [56][57][58][59] The constraints that canalize cells towards their stable phenotypic state appear to be in large part direct or long-range cellular interactions. Signaling from receptors at the cell surface is probably at the origin of the chromatin stabiliza-tion process via post-translational modifications of proteins interacting with DNA.…”
Section: Cellular Stochasticity Decreases During Differentiationmentioning
confidence: 99%